Oxidation-Induced Destabilization of Model Antibody-Drug Conjugates - Bücheler, Jakob; Winzer, Matthias; Weber, Christian; Gieseler, Henning (Journal of Pharmaceutical Sciences, 2019)
Oxidation of biopharmaceutics represents a major degradation pathway, which may impact bioactivity, serum half-life, and colloidal stability. This study focused on the quantification of oxidation and its effects on structure and colloidal stability for a model antibody and its lysine (ADC-L) and cysteine (ADC-C) conjugates. The effects of oxidation were evaluated by a forced degradation study using H2O2 and a shelf-life simulation, which used degrading polysorbate 80 as source for reactive oxygen species. Differential scanning fluorimetry revealed decreasing transition temperatures of the CH2 domain with rising oxidation, resulting in a loss of colloidal stability as assessed by size-exclusion high pressure liquid chromatography. The conjugation technique influences structural changes of the monoclonal antibody (mAb) and subsequently alters the impact of oxidation. ADC-C was most effected by oxidation as the CH2 domain showed the biggest destabilization on conjugation compared to the mAb and ADC-L. Quantification of Fc methionine oxidation by analytical protein A chromatography revealed 4-fold higher oxidation after 8 weeks for the ADC-C compared to the mAb. Payload degradation was observed independently of the conjugation technique used or if free in solution by ultraviolet-visible. In addition, adding antioxidants can be a suitable approach to prevent oxidation and achieve baseline stabilization of the proteins. (c) 2019 American Pharmacists Association (R). Published by Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2019-03-15